(untitled) (Economics and region, 2019)
The analysis of the stock market of Ukraine was conducted. The peculiarities and main problems of functioning and perspective directions of development of the stock market in the conditions of the national economy are determined. It is substantiated that the stock market is the main financial market which able to accumulate financial resources, as well as an important tool for conducting innovation policy. It is determined that the perspective direction for development of the concept of regulation of the stock market will include a mechanism for increasing the capitalization. Liquidity and transparency of the stock market also will be the priority direction of development. As follows it will ensure improvement of market infrastructure and its reliable and efficient functioning; improvement of mechanisms of state regulation and protection of investors’ rights.